AN OVERVIEW ON LOW LESAR THERAPY IN DISTAL RADIUS FRACTURE (Journal of Pharmaceutical Negative Results, 2022)
Several therapeutic procedures have been proposed to improve the current management of fractures. Low lesar treatment appears to be linked to pain relief and improved function and bone regeneration. Regardless of the settings or the usage of biomaterials, a low-level laser promotes the procedures of bone defect repair, according to data. However, standardizations are yet lacking, and additional research is needed to reach more definitive conclusions about the usage of low-level lasers. Low-power laser treatment is the assimilation of laser beam at the electronic level with in visible to near-infrared spectral spectrum without the generation of heat (390-1100 nm). It's used to manage healing of wounds, inflammation, and pain reduction, among other things. Despite its potential benefits, the use of lasers for health purposes is still controversial in mainstream medicine. The study's goal is to present a full picture of current research in the area in light of the potential influence at the molecular level, while taking into consideration the physical characteristics of various types of lasers used in bone fractures.